Analisis Makna Leksikal dan Gramatikal Pada Lagu “Kembali Pulang” Karya Suara Kayu dan Feby Putri : Kajian Semantik - Aini Fitri Rohmatul Ilmi; Rani Jayanti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The study of meaning in language, whether found in words, phrases, or sentences, is known as semantics. Language often has diverse or metaphorical meanings in literary works such as songs, which can confuse listeners. This becomes a problem when listeners understand song lyrics differently from what the artist intended. The song “Kembali Pulang” by Suara Kayu and Feby Putri, which is currently popular, is an example of lyrics rich in symbolism and meaning, making it interesting to study semantically. Abdul Chaer's semantic theory, which focuses on determining lexical and grammatical meaning, forms the basis of this approach. Lexical meaning, which includes synonyms, antonyms, homonyms, hyponyms, polysemy, redundancy, and ambiguity, is the dictionary meaning or actual meaning. However, meanings that have undergone composition, reduplication, and affixation are known as grammatical meanings. To correctly and thoroughly understand the message conveyed by the song “Kembali Pulang” by Suara Kayu and Feby Putri, this study aims to clarify the lexical and grammatical meanings contained in the song lyrics. A descriptive qualitative approach was used in this study, which included analysis of the song lyrics along with recording, listening, and reading strategies.